Emotions detection on an ambient intelligent system using wearable devices - Costa, Ângelo Gonçalo Araújo Silva (2019)
This paper presents the Emotional Smart Wristband and its integration with the iGenda. The aim is to detect emotional states of a group of entities through the wristband and send the social emotion value to the iGenda so it may change the home environment and notify the caregivers. This project is advantageous to communities of elderly people, like retirement homes, where a harmonious environment is imperative and where the number of inhabitants keeps increasing. The iGenda provides the visual interface and the information center, receiving the information from the Emotional Smart Wristband and tries achieve a specific emotion (such as calm or excitement). Thus, the goal is to provide an affective system that directly interacts with humans by discreetly improving their lifestyle. In this paper, it is described the wristband in depth and the data models, and is provided an evaluation of them performed by real individuals and the validation of this evaluation.